ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA PADA MATERI FUNGSI - Iffi Martin; Gida Kadarisma (IKIP Siliwangi, 2020)
This study aims to describe students’ problem solving abilities in the function material. This research is a qualitative descriptive study. The subjects of this study were 15 students of class X students of Muhammadiyah 1 Cimahi High School. The method used to collect data is by using written worksheets with mathematical problem solving abilities at the function table. The results showed that the ability to solve mathematical problem solving in class X high school Muhammaiyah was already high, as seen from the presentation stating that students were able to identify known elements, implement strategies and develop mathematical models. Overall students mathematical problem solving abilities, especially in material function are in high qualifications.